2005
DOI: 10.1111/j.1525-1497.2005.0191.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and incidence of intimate partner violence in older women in primary care practices

Abstract: Physical and sexual abuse by an intimate partner does occur in women over 55 years, but rates are lower than those of younger women. Health care providers are reminded to think about IPV in older women and to ask about abuse as disclosure is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 37 publications
(54 reference statements)
1
55
0
1
Order By: Relevance
“…A possible explanation for such variation could be that in our case both IPV types (physical and psychological) have been accounted for as an excluding category. On the other hand, in a study with women aged 55 and older who attended primary healthcare services, the estimates were lower: 3.6% for physical and sexual IPV and 2.6% for psychological IPV, although it must be pointed out that exposure to IPV was estimated from 55 years old and onwards (Zink et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A possible explanation for such variation could be that in our case both IPV types (physical and psychological) have been accounted for as an excluding category. On the other hand, in a study with women aged 55 and older who attended primary healthcare services, the estimates were lower: 3.6% for physical and sexual IPV and 2.6% for psychological IPV, although it must be pointed out that exposure to IPV was estimated from 55 years old and onwards (Zink et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…Other studies, however, found that women experienced significantly more threats and physical mistreatment from the age of 55 (Zink & Fisher, 2006). A study among women over 55 found that physical and sexual IPV is less frequent in older than in younger women (Zink, Fisher, Regan, & Pabst, 2005), while another study revealed that the frequency among women over 65 is similar to the frequency detected among younger women . Those contradictions may be explained by the definition of violence and how this violence has been assessed, the culture, age distribution of the population studied, length of the observation period, and the sampling extraction methodology used (Ruiz-Pérez, Plazaola-Castaño, & Vives-Cases, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…However, initiatives require agencies and individuals to recognise the issues surrounding domestic abuse and older women before they can be effective. This is echoed by Zink et al (2004Zink et al ( , 2005 who highlight that healthcare providers need to be alert to domestic abuse as an issue for older women in consultations as older women are often reluctant to disclose this type of information. They highlight that in addition to the reasons for non-disclosure identified with younger women, they are further compounded with older women through generational factors such as notions of privacy surrounding the home and intimate relationships.…”
Section: Potential Barriers To Older Women Reporting Domestic Abusementioning
confidence: 99%
“…31 Zink et al (2005) Telephone survey collected self-report information about health and abuse among women aged 55 years and over (n = 995)…”
Section: Potential Barriers To Older Women Reporting Domestic Abusementioning
confidence: 99%
“…In the context of elder violence, that which has been committed by an intimate partner has been less investigated, and, when addressed, is considered less severe than when applied to young women 5,6 . However, in US studies, women older than 55 years were more affected by IPV than younger women 7 , with intimate partners accounting for 13-50% of the abuse committed 8 . Similarly, in Spain, 29.4% of elderly women suffered this type of violence 9 .…”
Section: Introductionmentioning
confidence: 95%